FROM THE HISTORY OF MATHEMATICS TEACHING METHODOLOGY (THEORY AND PRACTICE) - Raxmonov Ixtiyor Xusanovich; Xalmanov Ural Rasulovich (Journals Park Publishing, 2022)
The article talks about theoretical and practical approaches to mathematics teaching methodology. In order to reveal the topic of the article, the scientific and research developments of foreign and local scientists were used. Conclusions from the topic of the article can be used in mathematics lessons.